Practicality of e-student worksheets on moss plant (bryophyta) material to improve critical thinking ability in MAN 3 Banjarmasin - Nurul Fajriyah; Khairunnisa Khairunnisa; Ita Ita (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2024)
The Electronic Student Worksheet (E-LKPD) on the topic of moss plants is a teaching material developed into an electronic medium to enhance students' critical thinking skills. However, it has not yet undergone practicality testing. This study aims to describe the practicality results of developing the student worksheet on the topic of moss plants (Bryophyte) as teaching material to improve students' critical thinking skills at MAN 3 Banjarmasin. This research employs the Education Design Research (EDR) method with Tessmer's formative evaluation, limited to individual tests (one-to-one) and small group evaluations. The research data were collected using a content practicality questionnaire and an expected practicality questionnaire. The results show that the content practicality achieved an overall average score of 95.83% (very good/feasible), while the expected practicality achieved an overall average score of 97.22% (very good). Based on these findings, it can be concluded that all aspects of practicality scored within the "very good" category, making the E-LKPD both feasible and practical for use. This study contributes significantly to the development of digital learning media aligned with students' needs in enhancing critical thinking skills. Abstrak. Lembar Kerja Peserta Didik Elektronik (E-LKPD) pada materi tumbuhan lumut adalah media pembelajaran yang dikembangkan menjadi media elektronik agar peserta didik mampu meningkatkan keterampilan berpikir kritis, akan tetapi belum memiliki uji kepraktisan. Penelitian ini bertujuan untuk mendeskripsikan hasil kepraktisan pengembangan LKPD pada materi tumbuhan lumut (Bryophyta) sebagai bahan ajar dalam meningkatkan keterampilan berpikir kritis peserta didik di MAN 3 Banjarmasin. Jenis penelitian ini menggunakan Education Design Research (EDR) dengan evaluasi formatif Tessmer yang dibatasi hingga tes perorangan (one-to-one) dan tes kelompok kecil (small group evaluation). Data penelitian ini berupa lembar angket kepraktisan isi dan lembar angket kepraktisan harapan. Hasil penelitian ini memperoleh hasil kepraktisan isi dengan skor rata-rata keseluruhan 95,83% (sangat baik/layak) dan hasil kepraktisan harapan dengan skor rata-rata keseluruhan 97,22% (sangat baik). Berdasarkan hasil penelitian ini, dapat disimpulkan bahwa semua keterampilan memiliki skor penilaian dalam kategori sangat baik sehingga E-LKPD layak dan praktis digunakan. Penelitian ini memberikan kontribusi signifikan dalam pengembangan media pembelajaran digital yang relevan dengan kebutuhan peserta didik dalam meningkatkan keterampilan berpikir kritis.